Ecological Immunological Adaptation in Traditional Communities: Biological Strategies to Environmental Risks - Rischi Utami, Ayu (Oshada, 2025)
This study investigates ecological immunological adaptation in traditional communities, focusing on how biological strategies are shaped by cultural practices and environmental interactions. Traditional populations living in close contact with natural environments face persistent ecological risks, yet demonstrate resilience through practices rooted in Traditional Ecological Knowledge (TEK). A qualitative ethnographic case study design was employed, with purposive sampling targeting key informants such as elders, traditional healers, and household representatives. Data were collected through in-depth interviews, focus group discussions, participant observation, and documentation of field notes and local archives. Data were analyzed using thematic analysis, involving coding and triangulation to identify recurrent cultural and ecological patterns influencing immunological resilience. Findings reveal that adaptive strategies emerge in three major dimensions: ecological cognition and ritualized health practices, dietary diversity including traditional fermentation and medicinal plants, and communal solidarity in managing ecological risks. These strategies represent a biocultural system where immunity is reinforced not only by biological exposures but also by cultural interpretation and collective action. In conclusion, ecological immunological adaptation in traditional communities highlights the interdependence of environment, culture, and health. Preserving TEK is essential for sustaining biocultural resilience and can inform One Health approaches in the face of climate change and global health challenges.